A positive synergetic effect observed in the P3HT–SnO2 composite semiconductor: the striking increase of carrier mobility. Issue 3 (4th January 2016) - Geng, Yujing; Zhao, Tianyu; Lian, Gang; Cui, Xinhang; Liu, Yang; Liu, Jinli; Wang, Qilong; Cui, Deliang
Abstract : A P3HT–SnO2 PNS composite semiconductor with extra-high mobility was prepared via the positive synergetic effect between organic and inorganic moieties. Abstract : Although the mobility of poly-3-hexylthiophene (P3HT) (10 −3 to 10 −2 cm 2 V −1 s −1 ) is far lower than that of SnO2 (10 2 cm 2 V −1 s −1 ), a novel P3HT–SnO2 composite semiconductor, exhibiting a strikingly positive synergetic effect between organic and inorganic moieties, was prepared by combining P3HT with SnO2 porous nanosolid (SnO2 PNS). The experimental results indicate that, after the formation of the composite semiconductor, the electron concentration increased by two orders and the mobility was up to 37 times as high as that of pristine SnO2 PNS. Furthermore, it was found that the electron concentration of the composite semiconductor was determined by both the content of P3HT and the number of chemical bonds at the P3HT–SnO2 interface, while mobility was mainly determined by the mobility of SnO2 PNS. Besides, thermal activation could increase the concentration and mobility of this composite semiconductor to some extent. By analyzing the experimental results, it is reasonable to believe that the electron transfer from P3HT to SnO2 PNS, together with the continuous connected structural characteristic of the latter, are responsible for the above novel phenomenon. This phenomenon may be of great helpful in the preparation of extra-high mobility organic–inorganic composite semiconductors, thus greatly improving the performance of optoelectronic devices.